Aspiration versus retention ultrasound-guided ethanol sclerotherapy for treating endometrioma: A retrospective cross-sectional study - Aflatoonian, Abbas (Int J Reprod Biomed, 2020)
BACKGROUND: Endometrioma is a common high-recurrence gynecological disease that affects infertility. Surgical resection using laparotomy or laparoscopy is applied as a standard treatment. Moreover, sclerotherapy is reported to be effective as a non-invasive method for treating endometrioma. OBJECTIVE: To evaluate whether the ethanol retention or aspiration after sclerotherapy improve pregnancy outcome in infertile women with endometrioma. MATERIALS AND METHODS: In a retrospective study, hospital records of 43 women with recurrent or bilateral endometrioma who had been undergone transvaginal ultrasound sclerotherapy were reviewed. They were selected to receive either ethanol for 10 min, ethanol injection, irrigation, and then aspiration or total retention without aspiration based on the surgeon's decision. The participants were followed-up for 3, 6 and 12 months for natural or artificial conception as well as for cyst recurrence. RESULTS: Chemical pregnancy was positive in 52% of the women in the aspiration group and 53.8% in the retention group. Ongoing pregnancy (44% vs 46.2%, p = 0.584) and live birth (40% vs 46.2%, p = 0.490) were reported marginally higher in the retention group compared with the aspiration group, and the differences were not statistically significant. Moreover, the recurrence rate were found to be 48.1% and 37.5% in the aspiration and retention groups, respectively (p = 0.542). The cysts size in the retention group was significantly correlated to the recurrence rate. CONCLUSION: Both the aspiration and left in situ of ethanol 95% sclerotherapy have the similar impact on the treatment of ovarian endometrioma regarding pregnancy and recurrence rate. However, larger randomized studies with strict inclusion criteria are needed.